Study on Preparation of Sponge Rubber Using in Bicycle and Motorcycle Tire - No Air - Tran, Thi Nga; Nguyen, Quang Hao; Nguyen, Viet Hung (Old Journal, 2018)
In this paper, preparation of sponge rubber using in bicycle/motorcycle tire was studied. It was shown that rubber mixture X5, at constant content of additives, with the 25phr of inorganic filler and 20 phr of foamer can meet requirements of Vietnamese standards on bicycle/motorcycle tire. Moreover, these mixtures were in same level in comparison with samples from imported tires. Testing of produced tires show that mixture X5 are suitable for technological line and can be used for sponge tire (no air) production in SRC.